2010
DOI: 10.1002/jsfa.3799
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activities of essential oils and extracts of TurkishAchillea, SaturejaandThymusspecies against plant pathogenic bacteria

Abstract: Our results demonstrate that S. spicigera, T. fallax oils, carvacrol and thymol could become potentials for controlling certain important agricultural plant pathogenic bacteria and seed disinfectant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 25 publications
1
69
0
Order By: Relevance
“…Among previously published studies, the antibacterial activity of thymol-containing oil of O. gratissimum was only reported in the work of Ngassoum and co-authors 37 against some Gramnegative and Gram-positive bacteria other than L. monocytogenes and S. Typhimurium. Thymol was also previously shown to possess antimicro-bial activities [42][43][44][45] and inhibition diameters obtained for thymol in the same concentration as in the different oils show that it is responsible for an important part of the activity, but other antimicrobial components are also present.…”
Section: Antibacterial Activity Of Essential Oilsmentioning
confidence: 87%
See 1 more Smart Citation
“…Among previously published studies, the antibacterial activity of thymol-containing oil of O. gratissimum was only reported in the work of Ngassoum and co-authors 37 against some Gramnegative and Gram-positive bacteria other than L. monocytogenes and S. Typhimurium. Thymol was also previously shown to possess antimicro-bial activities [42][43][44][45] and inhibition diameters obtained for thymol in the same concentration as in the different oils show that it is responsible for an important part of the activity, but other antimicrobial components are also present.…”
Section: Antibacterial Activity Of Essential Oilsmentioning
confidence: 87%
“…In this study, the highest antibacterial activity corresponded to the highest content in carvacrol (30.8 %) present in oil of O. canum harvested at 19h. Tests realized with pure carvacrol, known to possess antimicrobial activities [42][43][44][45] showed that it can almost completely explain the antibacterial activity of the oils.…”
Section: Antibacterial Activity Of Essential Oilsmentioning
confidence: 99%
“…Karanja et al [40] also identified hexacosane from a novel Streptomyces isolate, RUJ7-1, from Ruma National Park by GC-MS analysis. Hexacosane has been shown to exhibit potent antibacterial activity against 25 phytopathogenic bacterial strains [54] and antioxidant activity [55]. Stearic acid 2-hydroxy-1-(hydroxymethyl) ethyl ester has antifungal activity [56].…”
Section: Gc-ms Spectroscopymentioning
confidence: 99%
“…The essential oil of this plant shows various biological activities such as anti-oxidant, antibactial properties. These activities have been mainly attributed to constituents such as thymol, carvacrol, borneol, terpinenchemo type and spathulenol (Baser et al, 1993;Gormez et al, 2016;Goze et al, 2009;Kotan et al, 2010).…”
Section: Sirmentioning
confidence: 99%